2018
DOI: 10.1002/jcp.26918
|View full text |Cite
|
Sign up to set email alerts
|

MFG‐E8 reverses microglial‐induced neurotoxic astrocyte (A1) via NF‐κB and PI3K‐Akt pathways

Abstract: Recent evidence have suggested that neuroinflammation and ischemia induce the activation of two different types of reactive astrocytes, termed A1 and A2. Additionally, A1 astrocytes contribute to the death of neurons and oligodendrocytes in neurodegenerative diseases, such as Alzheimer's disease (AD). In the current study, we constructed an Aβ42-activated microglia-conditioned medium to induce A1 astrocytic activation via secretion of interleukin 1α, tumor necrosis factor, and complement component 1q in vitro,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(93 citation statements)
references
References 35 publications
3
90
0
Order By: Relevance
“…As well as releasing a potent neurotoxin, A1 astrocytes were less able to promote the formation of new synapses, and caused a decrease in the excitatory function of CNS neurons 35 . Recently more and more researches indicate that A1 astrocytes may encourage the development of neurodegenerative diseases, such as Alzheimer's disease (AD), Huntington's disease, Parkinson's disease, amyotrophic lateral sclerosis, and multiple sclerosis (MS), and block of A1 astrocyte conversion by microglia is neuroprotective 35,[69][70][71] . The A2 astrocyte-related gene S100A10 is essential for cell proliferation, membrane repair, and inhibition of cell apoptosis 35 .…”
Section: Discussionmentioning
confidence: 99%
“…As well as releasing a potent neurotoxin, A1 astrocytes were less able to promote the formation of new synapses, and caused a decrease in the excitatory function of CNS neurons 35 . Recently more and more researches indicate that A1 astrocytes may encourage the development of neurodegenerative diseases, such as Alzheimer's disease (AD), Huntington's disease, Parkinson's disease, amyotrophic lateral sclerosis, and multiple sclerosis (MS), and block of A1 astrocyte conversion by microglia is neuroprotective 35,[69][70][71] . The A2 astrocyte-related gene S100A10 is essential for cell proliferation, membrane repair, and inhibition of cell apoptosis 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that amyloid-β (Aβ) directly activated astrocytic NF-κB and C3 release, consistent with the high expression of C3 seen in patients with Alzheimer's disease (32). Moreover, the Aβ-activated microglia CM also induced A1 harmful astrocytes via the NF-κB signaling pathway (27). In addition, ROS is known to be implicated in driving astrocyte reactivity and regulating NF-κB activation (20,21).…”
Section: Discussionmentioning
confidence: 80%
“…Afterward, the supernatant containing microglia was obtained and re-plated on PDL-coated T-asks. For the astrocyte culture, the ask with mixed glial cultures was shaken for another 3 h at 250 rpm to remove OPCs, and then puri ed astrocytes were obtained (27,28).…”
Section: Primary Microglia and Astrocyte Culture And Treatmentmentioning
confidence: 99%
“…Two proteins, MFG-E8 and SPARC, are down-regulated in the presence of Rapa at 48 hpt (Table 2). These proteins have been associated with astrocyte-synapse and astrocyte-endothelial cell interactions and in the suppression of A1 reactive astrocytes via the up-regulation of PI3K-Akt and the down-regulation of nuclear factor-κB pathways [34,35]. MFG-E8 also has a protective role against Alzheimer's Disease by upregulating the induction of neurogenesis and neural stem cell proliferation [36].…”
Section: Implications Of Bafa1/rapa-dysregulated Intracellular Astrocmentioning
confidence: 99%